Identification of a novel alkenone in Black Sea sediments - Xu, L.; Reddy, C. M.; Farrington, J. W.; Frysinger, G. S.; Gaines, R. B.; Johnson, C. G.; Nelson, R. K.; Eglinton, T. I. (Organic Geochemistry, 2001)
We report the identification of a novel long-chain ketone in Holocene Black Sea sediments. Based on chemical properties, and chromatographic and mass spectrometric characteristics, this compound has been identified as a diunsaturated C-36 ethyl ketone. Further analyses indicated the position and configuration of the double bonds, and the novel alkenone was determined to be hexatriaconta-(16E,21E)-dien-3-one. While this compound is present in only trace quantities in Unit I sediments, it is the most abundant alkenone in portions of Unit II. Its presence thus apparently pre-dates the invasion of Emiliania huxleyi in the Black Sea. The down-core profiles and isotopic compositions suggest that the precursor for the C-36:2 alkenone may be distinct from that of the C37-39 alkenones, however the biological origin of this novel compound is presently unknown. (C) 2001 Elsevier Science Ltd. All rights reserved.
id: 1946; PT: J; UT: WOS:000168692100002